2019
DOI: 10.1038/s41377-019-0181-7
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive determination of murine placental and foetal functional parameters with multispectral optoacoustic tomography

Abstract: Despite the importance of placental function in embryonic development, it remains poorly understood and challenging to characterize, primarily due to the lack of non-invasive imaging tools capable of monitoring placental and foetal oxygenation and perfusion parameters during pregnancy. We developed an optoacoustic tomography approach for real-time imaging through entire ~4 cm cross-sections of pregnant mice. Functional changes in both maternal and embryo regions were studied at different gestation days when su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 44 publications
0
25
1
Order By: Relevance
“…We saw minimal changes in placental oxygenation at different arterial oxygenations. Our PAFT data indicating that there were minimal changes in the relative sPO 2 of the placentas, in comparison to changes in the maternal common iliac artery, is different from previously published photoacoustic imaging studies from Arthuis et al [ 43 ] and Basak et al [ 26 ]. However, the Arthuis et al group used 5% oxygen to create a hypoxic condition which likely led to their observed greater reduction in placental sPO 2 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We saw minimal changes in placental oxygenation at different arterial oxygenations. Our PAFT data indicating that there were minimal changes in the relative sPO 2 of the placentas, in comparison to changes in the maternal common iliac artery, is different from previously published photoacoustic imaging studies from Arthuis et al [ 43 ] and Basak et al [ 26 ]. However, the Arthuis et al group used 5% oxygen to create a hypoxic condition which likely led to their observed greater reduction in placental sPO 2 .…”
Section: Discussioncontrasting
confidence: 99%
“…Indocyanine green (ICG) dye, a widely used contrast agent in both fluorescence and photoacoustic imaging [ 21 ], is an FDA approved dye with high absorption in the near infrared (NIR) range. Free ICG has been used in PAT imaging to observe blood perfusion [ 22 ], and pharmacokinetic monitoring in multiple organs [ 23 ] and brain vasculature [ 24 ], superficial human finger vasculature [ 25 ], placental perfusion [ 26 ]. Targeted ICG contrast agents have also been used to analyze passive ICG accumulation in tumor microenvironment [ [27] , [28] , [29] , [30] ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has recently been suggested that dimorphisms, e.g., placental and fetal sex, exist which have an impact on placental development and fetal growth [35,36]. Furthermore, when collecting physiological data from embryos in utero or investigating feto-placental units in genetically modified dams, differences between each feto-placental unit can be observed regarding heart rate [37] or normal fetal development independent of fetal genotype [38], respectively, suggesting that analyzing multiple placentas per dam could be appropriate. Lastly, each placenta has a certain individual reserve capacity to support proper fetal growth that is independent of the dam [39].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, if the oxygenation of the murine placenta behaved like the human placenta, with a positive correlation between placental oxygenation and gestational age, our hypothesis should be tested at an early stage of pregnancy ( 108 ). However, the oxygenation of the murine placenta does not undergo particular variations in the period between 10 and 18 days of pregnancy ( 118 ). In contrast, the lowest oxygen values appear to be observed around the eighteenth day of pregnancy ( 119 ).…”
Section: Discussionmentioning
confidence: 99%